Research on High-speed EMUs Lateral Stability - Chuang LIU; Tao LIU; Qingli HAN; Jun FAN; Liang DUAN (机车电传动)
The lateral stability of high-speed EMUs is related to passenger comfort and even safety. Summarizing the experience of high-speed railway operation in recent years, the mechanism, influencing factors and solving measures of lateral stability of high-speed EMUs were studied through theoretical research, simulation analysis and application test. It was concluded that: the dynamic stiffness of anti-snake absorber has a great influence on the lateral stability of the vehicle; the main reason for the high-frequency snake vibration of the bogie is the poor matching between the local track position and the not full rail head after the wheel tread wear, which could effectively improved by maintaining the wheel and rail status regularly.